Sotalapsien paikka(tunne) - Kuusisto-Arponen, Anna-Kaisa (Alue ja Ympäristö, 2007)
During the war years in Finland (from 1939 to 1945) around 70 000–80 000 Finnish children were sent to foster families in Sweden, Denmark and Norway. The years abroad had an enormous effect on these children’s sense of belonging to community and place. In this article I focus on the sense of place among Finnish war children. Sense of place develops through lived experiences of spatiality, particularly of everyday places. In war children’s case several forced displacements created fractions in experiencing spatiality and everyday places. To capture the multidimensionality of experiential place, I utilise theoretical discussions of politics of place and geography of khora. In other words, I discuss how sense of place is formed through conscious and unconscious processes. Jacques Derrida’s one interpretation of khora is a half-way-place, which is midway between space and time. I suggest that the unconscious processes of war children’s sense of place can be partly viewed as a half-way-place. Empirically, my aim is to trace the secondary impressions of khora‘s half-way-place.